JAMAK PRAYERS WHEN PERFORMING A WEDDING RECEPTION PERSPECTIVE MA'ANIL HADIS (International Conference on Social and Islamic Studies, 2022)
Akad and wedding receptions are moments that are considered sacred and are eagerly awaited by a million people today. Not a few think that this moment is a very important moment than anything, even the implementation is very luxurious and lively. Implementation which often takes all day just to welcome guests who come with various properties that cannot be separated from the joy of this moment. And it's so important, most people dare to put aside the obligation to pray just for the sake of maintaining the makeup on the bride. Prayer is one of the acts of worship with the fardhu ain law, which however and whatever the conditions must be carried out. As explained in the Book of Fathul Qarib page 20 that even in a situation on the battlefield, members of the war are still required to pray according to the provisions stipulated in the book. And is it only because the moment of marriage that is considered important makes it understandable to leave or join the prayer? Though marriage also includes worship that will be carried out for life and must be maintained by its wisdom by not leaving prayer. Then a concrete solution is needed in this case. So this research intends to strengthen the obligation to pray when on the move, especially in the implementation of wedding processions and eliminate the trivial notion of postponing prayers only for certain reasons. This type of research is descriptive qualitative, namely by using literature review, especially in the perspective of hadith and also equipped with interviews from several related sources to support the accuracy of the data. The results of this study are in the form of a legal basis and a solution to how important it is not to leave prayer when carrying out a wedding procession in the perspective of hadith.